2020
DOI: 10.1177/0898264320913450
|View full text |Cite
|
Sign up to set email alerts
|

Life-Course Trauma and Later Life Mental, Physical, and Cognitive Health in a Postapartheid South African Population: Findings From the HAALSI study

Abstract: Objective: To investigate the relationships between exposure to life-course traumatic events (TEs) and later life mental, physical, and cognitive health outcomes in the older population of a rural South African community. Method: Data were from baseline interviews with 2,473 adults aged ≥40 years in the population-representative Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa (HAALSI) study, conducted in 2015. We assessed exposure to 16 TEs, and used logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 62 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…The authors suggested that the more favorable outcomes observed in the stressor group may reflect resilience and coping skills, which may contribute to preserved cognitive functioning. In another study, Payne et al (2020) found that endorsing more stressful life events was associated with psychological outcomes including depression and PTSD, but not cognitive impairment. Taken together, although there are indications of potential associations between stressful experiences and cognitive outcomes, the current evidence is inconclusive.…”
mentioning
confidence: 96%
“…The authors suggested that the more favorable outcomes observed in the stressor group may reflect resilience and coping skills, which may contribute to preserved cognitive functioning. In another study, Payne et al (2020) found that endorsing more stressful life events was associated with psychological outcomes including depression and PTSD, but not cognitive impairment. Taken together, although there are indications of potential associations between stressful experiences and cognitive outcomes, the current evidence is inconclusive.…”
mentioning
confidence: 96%
“…Apartheid likely has different effects on an individual, dependent on their social position but also on how much of the apartheid regime they lived through. An existing study took a life course approach to describe the relationship between life course trauma and later life health and found that traumatic events were associated with higher odds of mental health conditions and physical disability (Payne et al 2020). The effect of apartheid is likely very different for someone who was born prior to and lived most their life under apartheid, compared to if someone was born towards the end.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, apartheid was in place from 1948-1994 (Chopra and Sanders 2004), meaning that the majority of our study sample spent most of their lives under apartheid, with some being old enough to experience pre-and post-apartheid society. This apartheid legacy has resulted in persistent health and social inequalities by gender, and across racial and socioeconomic strata (Bell et al 2022;Chopra and Sanders 2004;Coovadia et al 2009;Payne et al 2020). Some individuals may experience more or less of these inequalities depending on their social location, and their advantages or disadvantages may be amplified over time by changing historical and political contexts.…”
Section: Introductionmentioning
confidence: 99%
“… See Liebel (2020);Aitken (2018);Evans and Holt (2011);Skelton (2009);Horton et al, (2008); Onta-Bhatta (2001), for age-based discussions/debates on interdisciplinary influence shaping Children's Geographies/Childhood Studies.2 For more global interactions with Life Course Theory refer to;Payne et al (2020);Qin et al (2020);Wood et al (2018);Elder et al (2003).…”
mentioning
confidence: 99%
“… For more global interactions with Life Course Theory refer to; Payne et al. (2020); Qin et al. (2020); Wood et al.…”
mentioning
confidence: 99%